PENGEMBANGAN DISPOSISI DAN KEMAMPUAN KOMUNIKASI MATEMATIS MELALUI PENDEKATAN PROBLEM SOLVING DALAM PEMBELAJARAN DI MTs - Windharti, Vivin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis researchaimed to elucidate how is the development of students’ disposition and mathematical communication ability after Problem Solving approach is being applied in Integer Multiplication Oprations Lesson in 4th grade of MTs U shuluddin Singkawang. The research method used was pre-experimental with one grup pretest-posttest design. The samples werw the 34 students of Class VII b. According to Mann Whitney test by using SPSS 23.0, obtained the value of Sig. (2-tailed) = 0.00 ≤ α = 0.05, which means that there is a development in students’ disposition and mathematical communication ability after being treated with Problem Solving approach in Integer Multiplication Operations Lesson. Based on the computation of Effect Size, the contribution of Problem Solving approach on students’ mathematical disposition and mathematical communication is 49.62 % and 49.84 % respectively. Keywords: Mathematical Disposition, Mathematical Communication Ability, Problem Solving